2004
DOI: 10.17221/4303-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality in two hybrid slaughter lines of pigs

Abstract: ABSTRACT:We evaluated two hybrid slaughter lines, progeny of hybrid parent gilts (LW × L) and D or LW -sire line terminal boars. Within two trials (with a six-month interval between them) the data on 40 animals were acquired; 20 hybrid pigs were sired by Duroc and 20 by LW terminal boars. Post-mortem changes were described by pH, conductivity, redox potential, remission and drip loss. Dry ma�er, intramuscular fat and myoglobin content were determined. Sensory tests evaluated aroma, flavour and texture. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Armero et al (2002) and Oliver et al (2003) documented the highest content of IMF -2.89% in Duroc breed. Jandásek et al (2004) found out even 3.34% IMF in the hybrid combination (LW D × L) x D and 3.01% in the hybrid combination (LW D × L) × LW S . On the contrary, Mikule et al (2001) reported the IMF content 0.71/0.85% in the breed LW/L.…”
Section: Fatmentioning
confidence: 91%
“…Armero et al (2002) and Oliver et al (2003) documented the highest content of IMF -2.89% in Duroc breed. Jandásek et al (2004) found out even 3.34% IMF in the hybrid combination (LW D × L) x D and 3.01% in the hybrid combination (LW D × L) × LW S . On the contrary, Mikule et al (2001) reported the IMF content 0.71/0.85% in the breed LW/L.…”
Section: Fatmentioning
confidence: 91%
“…Especially important for increasing the economic efficiency of industrial meat production is the use of animals with high genetic potential, aimed at reducing the level of feed costs per unit of live weight gain. Gourmet food products can be obtained only from high-quality environmentally friendly raw materials [7,14].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the presence of Pietrain breed in crossbreeds (especially 50%) leads to an increase in the amount of meat in the carcasses, but often causes a de-terioration in meat quality, including its pH, WHC, and colour [Florowski et al 2006]. On the other hand, the use of the Duroc breed in commercial cross-breeding (especially at 50%) reduces the proportion of meat in the carcasses and increases the backfat thickness [Blanchard et al 1999, Edwards et al 2003, Šimek et al 2004, Li et al 2013, and has a positive effect on the quality of meat, most often as an increase in intramuscular fat [Jandásek et al 2004] and, as a result, an improvement in meat tenderness, greater WHC, and a darker colour [Šimek et al 2004], often accompanied by a higher pH.…”
Section: Introductionmentioning
confidence: 99%